2016
DOI: 10.1097/bpb.0000000000000207
|View full text |Cite
|
Sign up to set email alerts
|

Sacral fatigue fractures in children with sacral spina bifida occulta

Abstract: In this report, we present two cases of 9-year-old children with spina bifida occulta (SBO) of the sacrum, who were diagnosed with sacral fatigue fractures. In both patients, MRI showed a linear signal void and high signal in sacral ala on the short tau inversion recovery sequence. Sacral SBO at the same level of the sacral fracture was observed in each patient on computed tomography images. These lesions healed with rest. This is the first literature reporting cases with sacral stress fractures who had SBO at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Sakai et al 29 reported a significantly higher incidence of lumbar spondylolysis among patients with SBO than among those without SBO (16.2% vs 5.0%, respectively). Hama et al 8 presented 2 cases of sacral fatigue fracture in 9-year-old patients with SBO at each affected level. Thus, the presence of SBO may increase the risk of fatigue fractures by altering the mechanical stress on the lumbar spine and sacrum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sakai et al 29 reported a significantly higher incidence of lumbar spondylolysis among patients with SBO than among those without SBO (16.2% vs 5.0%, respectively). Hama et al 8 presented 2 cases of sacral fatigue fracture in 9-year-old patients with SBO at each affected level. Thus, the presence of SBO may increase the risk of fatigue fractures by altering the mechanical stress on the lumbar spine and sacrum.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated imaging findings such as laterality, Risser sign, presence of spina bifida occulta (SBO), and course of the fracture lines. The Kaeding-Miller classification system 8 for stress fractures (Table 1) was used to grade injury severity.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue fractures of the sacrum sometimes occur in young athletes due to repetitive stress loads [30] but are reported to be rare in children [31][32][33]. The condition is typically accompanied with low back-pain [31][32][33] and Hama et al [31] suggest a possible association with spina bifida occulta. The girl in our study reported no regular weekly training activity and she had no clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%